Nlrp2 deletion ameliorates kidney damage in a mouse model of cystinosis - Rossi, Marianna Nicoletta; Matteo, Valentina; Diomedi-Camassei, Francesca; De Leo, Ester; Devuyst, Olivier; Lamkanfi, Mohamed; Caiello, Ivan; Loricchio, Elena; Bellomo, Francesco; Taranta, Anna; Emma, Francesco; De Benedetti, Fabrizio; et al. (Frontiers in Immunology, 2024)
Cystinosis is a rare autosomal recessive disorder caused by mutations in the CTNS gene that encodes cystinosin, a ubiquitous lysosomal cystine/H+ antiporter. The hallmark of the disease is progressive accumulation of cystine and cystine crystals in virtually all tissues. At the kidney level, human cystinosis is characterized by the development of renal Fanconi syndrome and progressive glomerular and interstitial damage leading to end-stage kidney disease in the second or third decade of life. The exact molecular mechanisms involved in the pathogenesis of renal disease in cystinosis are incompletely elucidated. We have previously shown upregulation of NLRP2 in human cystinotic proximal tubular epithelial cells and its role in promoting inflammatory and profibrotic responses. Herein, we have investigated the role of NLRP2 in vivo using a mouse model of cystinosis in which we have confirmed upregulation of Nlrp2 in the renal parenchyma. Our studies show that double knock out Ctns-/- Nlrp2-/- animals exhibit delayed development of Fanconi syndrome and kidney tissue damage. Specifically, we observed at 4-6 months of age that animals had less glucosuria and calciuria and markedly preserved renal tissue, as assessed by significantly lower levels of inflammatory cell infiltration, tubular atrophy, and interstitial fibrosis. Also, the mRNA expression of some inflammatory mediators (Cxcl1 and Saa1) and the rate of apoptosis were significantly decreased in 4-6-month old kidneys harvested from Ctns-/- Nlrp2-/- mice compared to those obtained from Ctns-/-mice. At 12-14 months of age, renal histological was markedly altered in both genetic models, although double KO animals had lower degree of polyuria and low molecular weight proteinuria and decreased mRNA expression levels of Il6 and Mcp1. Altogether, these data indicate that Nlrp2 is a potential pharmacological target for delaying progression of kidney disease in cystinosis.